The interaction between lifestyle and blood pressure on Stroke: A cross-sectional study from Northern China - Jiantao Yu; Qiang Zhou; Yanyan Zhao; Haiying Chen; Huiyong Yu; Yuying Li; Xiuguo Zhang (PLoS ONE, 2026)
Objective This study aimed to explore and quantify the extent of interaction between lifestyle factors and systolic and diastolic blood pressure on stroke among adults over 65 years of age. This investigation sought to provide valuable insights into the multifactorial risk factors for stroke, with the ultimate goal of supporting clinicians in implementing more focused and comprehensive preventive strategies. Methods Data were obtained from the 2019 health examination records of community hospitals in northern China. A stratified cluster random sampling method was used to select a representative sample from resident health records within the essential public health service management system. Participants were categorized into four subgroups based on systolic and diastolic blood pressure levels. Odds ratios (ORs) with 95% confidence intervals (CIs) and trend tests were used to examine the association between blood pressure categories and incident stroke. In the lifestyle subgroup analysis, a multiplicative interaction model within binary logistic regression was employed to assess the effect of interactions between unhealthy lifestyles and different blood pressure levels on stroke. Results A total of 34,995 eligible subjects were included in the analysis, comprising 44.3% males (n = 15,484) and 55.7% females (n = 19,511). The age range was 65–103 years, with a mean age of 71.91 ± 5.65 years. After adjusting for confounding factors, systolic and diastolic blood pressure (both as continuous and categorical variables) showed a linear positive correlation with stroke incidence(Ptrend for SBP = 0.001; Ptrend for DBP = 0.001). In the lifestyle subgroup analysis, this positive correlation remained significant across most subgroups; Furthermore, Interaction and joint effect analyses revealed that elevated SBP/DBP and unhealthy lifestyle factors synergistically augmented stroke risk after multivariable adjustment. Conclusions This study demonstrated that elevated systolic and diastolic blood pressure were significantly associated with a higher incidence of stroke. A synergistic effect was observed between unhealthy lifestyle factors (such as smoking, alcohol consumption, obesity, and physical inactivity) and elevated blood pressure in increasing stroke risk. Smoking partially mediated the relationship between diastolic blood pressure and stroke. These findings highlight the potential benefit of integrated control strategies targeting both blood pressure and modifiable lifestyle factors.